A Third Treasury of Kahlil Gibran - Edited by Sherfan, Andrew Dib (London Mandarin, 1994)
A collection of romantic writings from the author of 'The Prophet'. The treasury includes Gibran's 'Mirrors of the Soul', 'The Wisdom of Kahlil Gibran and 'Wings of Thought'.
Include Notes and References
Keywords: Gibran, Kahlil, 1883-1931 -- Mysticism in literature -- Mysticism